Renal Artery Thrombosis Secondary to Blunt Abdominal Trauma with Accessory Renal Artery Supplying the Kidney Segment: A Rare Case Report - Li, Guang-yong; Gao, Yu; Li, Pei-jun; Li, Meng (Urology Journal, 2015)